Detecting implicit cues of aggressiveness in male faces in revictimized female PTSD patients and healthy controls. (September 2018) - Lieberz, Klara A.; Müller-Engelmann, Meike; Bornefeld-Ettmann, Pia; Priebe, Kathlen; Weidmann, Anke; Fydrich, Thomas; Geniole, Shawn N.; McCormick, Cheryl M.; Rausch, Sophie; Thome, Janine; Steil, Regina
Highlights: The use of an innovative method examining women's perception and preferred reactions to implicit facial cues of aggressiveness – the facial Width-to-Height Ratio. Revictimized women do not show impairments in perceiving and reacting to threat accurately, however, they rated all men as less aggressive. Revictimized women with histories of intimate partner violence rated men with larger fWHRs and higher values of aggression as more attractive than revictimized women without IPV histories. A reduced appraisal of threat signals and an attraction to wider-faced and more aggressive men might increase the risk for revictimization. Abstract: Victimized women are thought to have impairments in identifying risk and to have dysfunctional reactions to threatening situations, which increase the risk for revictimization. To investigate possible deficits in revictimized women, we used a method examining women's perceptions of an implicit facial cue of aggressiveness – the facial Width-to-Height Ratio (fWHR). We tested whether revictimized women show impairments in detecting aggressiveness in male faces by neglecting cues of fWHR and choosing a smaller preferred distance to men. Fifty-two revictimized PTSD patients and 52 healthy controls provided ratings of aggressiveness and attractiveness for 65 photographed men and chose their preferred distance towards 11 pictured men. Multiple regression analyses indicated that revictimized women do not show impairments in perceiving and reacting to cues of aggression accurately. Hierarchical linear models, however, indicated that revictimized women rated all men as less aggressive. Revictimized women with histories of intimate partner violence (IPV) rated men with larger fWHRs and higher values of actual aggression to be more attractive than did revictimized women without IPV histories. A reduced appraisal of threat signals as threatening and an attraction to wider-faced and more aggressive men might increase the risk for revictimization.